ALOPESIA AREATA DENGAN TERAPI KOMBINASI INJEKSI PLATELET-RICH PLASMA (PRP) DAN TRIAMSINOLON ASETONID INTRALESI (Media Dermato Venereologica Indonesiana, 2022)
Alopecia Areata (AA) is an autoimmune disease characterized by sudden hair loss from the scalp. Treatment of existing AA is difficult, so a combination of more than one therapeutic modality is needed. This is a case report of a 29-year-old man who complained of hair loss on the occipital and temporal right scalp, causing local baldness. Neither itching nor pain in the affected area. The patient was suffered from hair loss for the past two months. Based on anamnesis, physical examination, and other supporting examinations, the patient was diagnosed with AA. The management was given in the form of combination intralesional therapy and obtained a satisfactory result. Although the diagnosis of AA is quite easy, the treatment of AA tends to be difficult and remains a clinical challenge. This is due to the lack of randomized controlled trials for the management of AA and the psychological aspect of AA that can cause anxiety and depression. The combination therapy was given in the form of an intralesional injection of triamcinolone acetonide followed by an intralesional injection of platelet-rich plasma (PRP) at intervals of 3 weeks in each session. Satisfactory results are obtained after 5 months of combined intralesional therapy.